Cover Feature: In vivo Evaluation of an Engineered Cyclotide as Specific CXCR4 Imaging Reagent (Chem. Eur. J. 58/2017). Issue 58 (17th August 2017) - Lesniak, Wojciech G.; Aboye, Teshome; Chatterjee, Samit; Camarero, Julio A.; Nimmagadda, Sridhar
Abstract : Cyclotides are natural microproteins found in plants with a head‐to‐tail circular Cys‐knotted topology. This work reports the in vivo evaluation in mice of the MCoTI‐based cyclotide, MCo‐CVX‐5c, for the development of imaging agents that target CXCR4. A [ 64 Cu]‐DOTA‐labeled version of this cyclotide demonstrated high and significant uptake in U87‐stb‐CXCR4 tumors compared to the control U87 tumors. The cover art is by Isaac Mora. More information can be found in the Full Paper by Camarero, Nimmagadda et al. onpage 14469 .